Academic Fraud Among Students and The Role Of Whistleblowing System - Allo, Cici Girik; Yulianti, Ni Luh Putu Nita (Institute of Computer Science (IOCS), 2025)
The purpose of this study was to examine the perception of accounting students in disclosing academic fraud and the reasons why students do it in Merauke City so that students dare to become whistleblowers who reveal academic fraud within the campus. Using a quantitative approach by distributing questionnaires. The sample was students who had taken auditing courses 1 and 2, data analysis using multiple linear regression techniques. The results of the study were the influence of attitudes towards behavior in disclosing fraud in Merauke City had a significant positive effect, subjective norms in disclosing fraud in Merauke City did not have a significant effect, Behavioral Control of disclosing fraud in Merauke City had a significant positive effect and the level of seriousness of fraud in disclosing fraud in Merauke City did not have a significant effect. This study concluded that the reason students committed academic fraud was because of demands, pressure, temptations from their surroundings so that students always tried to do various ways to get maximum results or grades in the academic world by committing academic fraud.